Implementation of COVID-19 vaccination services in prison in six European countries: translating emergency intervention into routine life-course vaccination - Mazzilli, Sara; Cocco, Nicola; Petri, Davide; Moazen, Babak; Rosello, Alicia; D’Arcy, Jemima; Plugge, Emma; Baglietto, Laura; Murauer, Eva; Stöver, Heino; Trattonikolas, Tassos; Stylianou, Iakovos; et al. (BMC public health, 2024)
Evidence has shown that the risk of transmission of SARS-CoV-2 is much higher in prisons than in the community. The release of the COVID-19 vaccine and the recommendation by WHO to include prisons among priority settings have led to the inclusion of prisons in national COVID-19 vaccination strategies. Evidence on prison health and healthcare services provision is limited and often focuses on a single country or institution due to the multiple challenges of conducting research in prison settings. The present study was done in the framework of the EU-founded project RISE-Vac. It aimed to analyse the best practices and challenges applied in implementing COVID-19 universal vaccination services during the pandemic to support future expansion of routine life course vaccination services for people living in prison (PLP).